Molecular characterization of gonadotropin-releasing hormone (GnRH) genes and their role in reproductive system of Pangasius species - Zamri, Amirah Syafiqah; Sahadan, Fatin Nabilah; Zulperi, Zarirah; Syukri, Fadhil; Esa, Yuzine (Korean Society of Fisheries and Aquatic Sciences, 2024)
Application of commercial hormone failed to promote breeding in certain Pangasius species due to the differences of gonad-otropin-releasing hormone specific peptide with species-specific bioactivities. Gonadotropin-releasing hormone (GnRH) is a hypothalamic decapeptide in the reproductive system that plays a crucial role in the regulation of reproductive processes. This study was performed to determine and analyse the GnRH genes from commercially important Pangasius sp., Pangasianodon hypophthalmus and Pangasius nasutus. The GnRH1 and GnRH2 genes were amplified and cloned into TOPO vector, followed by phylogenetic analysis of a complete open reading frame (ORF) of GnRH genes. The GnRH1 and GnRH2 genes of P. hypophthal-mus and P. nasutus were detected at 300 bp and 360 bp, encoded for 81 and 87 amino acids, respectively. Amino acid sequence identities revealed high homology of P. hypophthalmus and P. nasutus GnRH1 and GnRH2 genes in comparison with other fish and vertebrates. Phylogenetic tree showed that fish from various families were aggregated into a group of the same order due to their highest identity similarities. It revealed that the vertebrate formed clusters and are grouped according to their GnRH decapeptide and GnRH-associated peptide (GAP) region, indicating a close relationship among GnRH decapeptide and GAP in different vertebrate species.